Community capacity and disaster resilience - Ebay, Jorge S. (2007)
This paper contends that disaster management practice, especially within Philippine contexts, needs to be suffused with community based principles and approaches that underline community capacity and resilience for coping and survival. It notes that the current disaster management system and practice in the Philippines remains top-down in orientation and does not give adequate latitude for community participation. Subsequently, it relegates community experiences to the sidelines which can otherwise served as rich repository of information and knowledge for an improved Philippine disaster management system. This paper argues that community capacities are a strategic resource for disaster management that need to be enhanced and developed to the full for effective vulnerability and disaster risk reduction. Through community organizing and mobilization initiatives, community capacities can be encouraged and harnessed. These capacities can effectively underwrite resilience to disasters. This is most important in the light of international and national initiatives that underscore community action in risk and vulnerability reduction programs.
Keywords: Disaster resilience